Cryosphere dynamic study of Hunza Basin using remote sensing, GIS and runoff modeling - Javeria Saleem; Amna Butt; Adnan Shafiq; Sheikh Saeed Ahmad (Journal of King Saud University: Science, 2020)
Climate change is currently a dangerous phenomenon that has deleterious economic, social and environmental impacts. Climatic fluctuations directly affect the hydrology of an area, which in turn plays a significant role in economy of any country. In Pakistan, River Indus serves as a major fresh water resource, the flow of this river is fed by glaciated ice and snow present in Karakorum, Himalayas and Hindukush ranges. Therefore, it is necessary to evaluate the cryosphere dynamics of the area in order to determine the impact of climate change so that the water resources will be managed efficiently. To this end, Moderate Resolution Imaging Spectroradiometer (MODIS) satellite imagery of 2010 was used for cryosphere study of Hunza Basin. Daily runoff discharge of Hunza Basin, meteorological parameters, remotely sensed data and Digital Elevation Model (DEM) were analyzed synergically in the Snowmelt Runoff Model (SRM). Finally, computed runoff was compared with measured runoff for model calibration. Analysis revealed high glacial melting during simulation period. This indicated that regional warming (caused due to climatic fluctuations which were primarily caused by anthropogenic activities) has affected the hydrology of the area.